Approach to the theme probability and geometric probability in high school mathematics books indicated by PNLD - Ritter, Denise; Bulegon, Ana Marli (Revista Hipótese, 2022)
This work aims to analyze how the content of Probability is approached and whether Geometric Probability is presented in PNLD 2015 Mathematics textbooks. Samples of High School Mathematics suggested by the Textbook Guide were analyzed. It was noticed that all collections seek to highlight the historical aspects of Probability and most present situations of its application. None of the collections addresses the concept of Geometric Probability and only two have exercises that require this knowledge in the resolution. It is believed that the analysis performed can contribute to the teaching process of Probability concepts, making their learning more effective.
Keywords: Didatic books; Math; PNLD; Analyze